Common bile duct stones: analysis of the videolaparoscopic surgical treatment - Santo,Marco Aurelio (2012)
CONTEXT: About 9% of the Brazilian population has gallstones and the incidence increases significantly with aging. The choledocholithiasis is found around 15% of these patients, and a third to half of these cases presented as asymptomatic. Once the lithiasis in the common bile duct is characterized through intraoperative cholangiography, the laparoscopic surgical exploration can be done through the transcystic way or directly through choledochotomy. OBJECTIVE: To evaluate the results and outcomes of the laparoscopic treatment of common bile duct lithiasis. METHODS: Seventy consecutive patients were evaluated. They prospectively underwent the treatment of the lithiasis in the common bile duct and the exploration ways were compared according to the following parameters: criteria on their indication, success in the clearance, surgical complications. It was verified that about ½ of the choledocholithiasis carriers did not show any expression of predictive factors (clinical antecedents of jaundice and/or acute pancreatitis, compatible sonographic data and the pertaining lab tests). The laparoscopic exploration through the transcystic way is favored when there are no criteria for the practice of primary choledochotomy, which are: lithiasis in the proximal bile duct, large (over 8 mm) or numerous calculi (multiple calculosis). RESULTS: The transcystic way was employed in about 50% of the casuistic and the choledochotomy in about 30%. A high success rate (around 80%) was achieved in the clearance of the common bile duct stones through laparoscopic exploration. The transcystic way, performed without fluoroscopy or choledochoscopy, attained a low rate of success (around 45%), being 10% of those by transpapilar pushing of calculi less than 3 mm. The exploration through choledochotomy, either primary or secondary, if the latter was performed after the transcystic route failure, showed high success rate (around 95%). When the indication to choledochotomy was primary, the necessity for choledochoscopy through choledochotomy to help in the removal of the calculi was 55%. However, when choledochotomy was performed secondarily, in situations where the common bile duct diameter was larger than 6 mm, the use of choledochoscopy with the same purpose involved about 20% of the cases. There was no mortality in this series. CONCLUSION: The laparoscopic exploration of the common bile duct was related to a low rate of morbidity. Therefore, the use of laparoscopy for the treatment of the lithiasis in the common bile duct depends on the criteria for the choice of the best access, making it a safe procedure with very good results.